Effect of Enterprise Social Media on Employee Creativity: Social Exchange Theory Perspective - Wang, Zhiwei; Hangeldiyeva, Mahri; Ali, Asad; Guo, Mengmeng (Frontiers in Psychology, 2022)
This study applied an artifact-centric view to investigate the consequences of enterprise social media usage. It investigates how enterprise social media usage influences employee creativity. A moderated mediation model is developed based on social exchange theory. The empirical sample of 238 employees is used to test the proposed model. Results of the empirical analysis performed using PROCESS macro of SPSS indicate that enterprise social media usage positively impacts employee creativity via the mediating mechanisms (i.e. leader-member exchange and support for innovation). Furthermore, social media usage frequency negatively moderates this impact of enterprise social media usage on employee creativity via leader-member exchange. Interestingly, the empirical analysis reveals that the impact of enterprise social media usage frequency strengthens the indirect effect that enterprise social media usage has on employee creativity via perceived support for innovation.